Unveiling immune checkpoint regulation: exploring the power of in vivo CRISPR screenings in cancer immunotherapy - Wang, Yuxiang; Khalil, Athar; Kamar, Amina; Du, Mengyan; Dinh, Trang; McFarland, Christopher; Wang, Zhenghe (Frontiers in Genetics, 2023)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer immunotherapy by reinvigorating antitumor immune responses, but their efficacy remains limited in most patients. To address this challenge and optimize ICI treatment, understanding the underlying molecular intricacies involved is crucial. The emergence of CRISPR-Cas9 technology has empowered researchers to precisely investigate gene function and has introduced transformative shifts in identifying key genes for various physiological and pathological processes. CRISPR screenings, particularly in vivo CRISPR screenings, have become invaluable tools in deciphering molecular networks and signaling pathways governing suppressive immune checkpoint molecules. In this review, we provide a comprehensive overview of in vivo CRISPR screenings in cancer immunotherapy, exploring how this cutting-edge technology has unraveled potential novel therapeutic targets and combination strategies. We delve into the latest findings and advancements, shedding light on immune checkpoint regulation and offering exciting prospects for the development of innovative and effective treatments for cancer patients.